Video supervised treatment of patients with pulmonary tuberculosis in a health care center in Lima. Pilot study - Peinado, Jesús (2022)
Objective: To report the characteristics of the implementation process of the video supervised treatment (VST) of patients with pulmonary tuberculosis in a first level health care center of the Social Security in Peru. Methods: An observational study was carried-out including patients enrolled from 18/09/2018 to 24/09/2019. Eight out of nine patients completed the VST, one patient was transferred to other institution before finishing treatment. One nurse trained at Partners in Health arranged the 727 video calls. Results: adherence to treatment was 100%. Conclusions: VST may be a useful alternative for patients with drug sensitive tuberculosis.